2020
DOI: 10.3390/rs12162596
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of PROBA-V Surface Albedo V1 for the Continuity of the Copernicus Climate Change Service

Abstract: The Copernicus Climate Change Service (C3S) includes estimates of Essential Climate Variables (ECVs) as a series of Climate Data Records (CDRs) derived from satellite data. The C3S Surface Albedo (SA) v1.0 CDR is composed of observations from National Oceanic and Atmospheric Administration (NOAA) Very High Resolution Radiometers (AVHRR) (1981–2005), and VEGETATION sensors onboard Satellites for the Observation of the Earth (SPOT/VGT) (1998–2014) and Project for Onboard Autonomy satellite (PROBA-V) (2014–2020),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Our results agree with the previous hypothesis, and indeed, the lower temporal resolution of C3S and GLASS may be one of the reasons of the superior performance of MCD43C3 over snow. The overestimation of snow-free albedo against stations, and also compared to MCD43C3, was also reported by Lellouch et al [51] and Sánchez-Zapero et al [52], particularly at regions covered by forests [38]. Our results suggests that this positive bias might exist in all types of land cover, since none of the stations used were surrounded by forests.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results agree with the previous hypothesis, and indeed, the lower temporal resolution of C3S and GLASS may be one of the reasons of the superior performance of MCD43C3 over snow. The overestimation of snow-free albedo against stations, and also compared to MCD43C3, was also reported by Lellouch et al [51] and Sánchez-Zapero et al [52], particularly at regions covered by forests [38]. Our results suggests that this positive bias might exist in all types of land cover, since none of the stations used were surrounded by forests.…”
Section: Discussionsupporting
confidence: 88%
“…C3S-v2 albedo improves during the snow-free season, reaching an accuracy level similar to that of MCD43C3, despite showing a small positive bias. C3S underestimation over snow was also observed by Song et al [19], Lellouch et al [51], Sánchez-Zapero et al [52] and Song et al [20], who suggested that the low temporal resolution and large compositing window hinder C3S capacity to detect snow events. Our results agree with the previous hypothesis, and indeed, the lower temporal resolution of C3S and GLASS may be one of the reasons of the superior performance of MCD43C3 over snow.…”
Section: Discussionmentioning
confidence: 56%
“…The Spectral Response Function (SRF) of MODIS, SPOT-VGT, and PROBA-V indicates the difference of band location, band width, and response percentage of input signal over similar spectral channels [59]. Compared with SPOT and PROBA -V, the MODIS sensor has narrower band width, especially at NIR and SWIR bands [60], which may enhance the difference at NIR albedo band over the vegetation region during leaf-on season as presented in the results section, and can also propagate into other broadband albedo values. The SRF shape of MODIS and SPOT is close to "Gaussian distribution", while that of PROBA -V shows an asymmetric shape with higher response percentage at the lower or upper range of each spectral regime [14,59], while the SPOT/VGT and PROBA-V channels provide very similar spectral characteristics in the Blue, Red and NIR bands, but the PROBA-V spectral response in SWIR band is narrower than that of SPOT/VGT [14], which may be one of the reasons inducing the albedo difference of CGLS at NIR and SW bands from June 2014 (Figure 4(A1,A2,B1,B2,C1,C2,D1,D2)).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surface albedo can be generated using the Bidirectional Reflectance Distribution Function (BRDF) with a kernel-driven model [18][19][20][21]. The short-period and multi-angle reflectance data required can be obtained from the MODerate Resolution Imaging Spectroradiometer (MODIS) [20], Polarization and Directionality of the Earth Reflectance (POLDER) [22], Visible Infrared Imaging Radiometer Suite (VIIRS) [23], Airborne Visible-InfraRed Imaging Spectrometer (AVIRIS) [24], VEGETATION (VGT) [25], PROBA-VEGETATION (PROBA-V) [25,26], or Spinning Enhanced Visible and Infrared Imagers (SEVIRI) [27]. However, these albedo products are too coarse to describe the detailed features of the surface, which hinders downstream calculations of surface processes such as land transformations [28], forest structure [29], fire extent and burn severity [30], and snow cover extent and melt [30][31][32].…”
Section: Introductionmentioning
confidence: 99%